SARS-CoV-2, Noroviruses, Adenoviruses, and Antibiotic-Resistant Coliforms Within Chilean Rural Wastewater Treatment Plants - Villamar-Ayala, C (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Wastewater-based epidemiology (WBE) is an effective tool for assessing health risks in rural areas with limited access to health care. Wastewater treatment plants (WWTPs) allow for the monitoring of pathogenic microorganisms, which is key to detecting viral integrity and bacterial viability to assess health risks. This study evaluated five rural WWTPs in Chile during 2022 in two seasons (autumn–winter and spring–summer). SARS-CoV-2, norovirus GI/GII, and HAdV-F40/41 was analyzed, along with antibiotic-resistant coliforms. Influent and effluent samples were used, with viral integrity analysis by propidium monoazide and culture methods to assess bacterial resistance. Despite the low number of clinical cases, SARS-CoV-2 was detected in all influent samples. Intact viral particles of NoV GI (78%), NoV GII (72%), and HAdV-F40/41 (65%) were found. This suggests that they may still be infectious. Viral removal ranged from 74% to 100%, although intact HAdV was detected in effluent (6.2%). Coliforms resistant to various antibiotics were detected and partially removed (22–100%). Removal efficiency depends on the type of treatment and the season of the year. WWTPs act as temporary reservoirs of infectious agents. This study reinforces the usefulness of WBE in rural contexts and WWTPs as barriers or not to these contaminants to the environment. © 2025 by the authors.